Zakat and the Concept of Ownership in Islam: Yusuf Qaradawiâs Perspective on Islamic Economics - Nurlaelawati, Euis (Al-Jamiah: Journal of Islamic Studies, 2010)
Looking at the two functions of ownership which include the individual and social, Qaradawi explores such a relationship and analyzes its implication for social justice. Zakat has multiple functions: the religious, economic, and social. It constitutes the earliest concept of mutual social responsibility proposed by Islam to achieve social justice. Zakat serves as a means to both guarantee social security and strengthen social solidarity. From this perspective, Qaradawi moves forward to link up the concept of zakat with the Islamic system of economics. The linkage between zakat and the Islamic system of economics is visible in the ways Qaradawi investigates various aspects of ownership and zakat in Islam. This can particularly be seen in his analysis that the concept of Islamic insurance coheres with the interpretation of al-gharimin, one of the groups deserving to the income of zakat and in his emphasis that mutual social responsibility, which aims to fulfill the needs of adequate livelihood, can be supplied only by zakat. This article argues that these views in turn confirm Qaradawiâs concern with the importance of zakat as the foundation of both the social and economic systems of Islam. This article also emphasizes that, for Qaradawi, different from voluntary charity that can only fulfill the minimum requirement of the needs of livelihood, zakat can supply the answer to cover all the needs of livelihood of Muslim society.